The Impact of Transformational Leadership on Employee Retention: Mediation and Moderation Through Organizational Citizenship Behavior and Communication - Tian, Hongyun; Iqbal, Shuja; Akhtar, Shamim; Qalati, Sikandar Ali; Anwar, Farooq; Khan, Muhammad Aamir Shafique (Frontiers in Psychology, 2020)
This study investigates the impact of transformational leadership on employee retention in small- and medium-sized enterprises (SMEs) and probes the mediating role of organizational citizenship behavior (OCB) and the moderating role of communication. Data were collected using convenience sampling from 505 employees of SMEs. A Smart PLS structural equation modeling (PLS-SEM) was used to estimate the various relationships. The findings of the study reveal a positive and significant relationship between transformational leadership and OCB. Similarly, this study finds a positive and significant relationship in OCB and employee retention. In addition, OCB had a positive mediating effect on the relationship between transformational leadership and employee retention. Furthermore, communication positively moderates the transformational leadership– OCB and OCB–employee retention relationships. Leaders at SMEs should implement the traits of transformational leadership such as developing a compelling vision for employees, focusing on goal achievement, having problem-solving techniques, having a sense of purpose, and spending time on the training and development of the team to enhance OCB and employee retention.